Theory and Evidence on the Resolution of Financial Distress - Brown, David T.; Ciochetti, Brian A.; Riddiough, Timothy J. (Review of Financial Studies, 2006)
We analyze a financially distressed owner-managed project. The main results of the model are: (1) borrower default is an endogenous response to the anticipated restructuring–foreclosure outcome; (2) the lender’s restructuring–foreclosure decision depends critically on the interaction between project value and industry liquidity; and (3) the lender waits for the industry to recapitalize before selling assets obtained through foreclosure. Empirical analysis of a large sample of defaulted commercial real estate loans supports many of the model predictions, including restructuring–foreclosure outcomes that are consistent with endogenous borrower default and firesale discounts that vary depending on industry market conditions at the time of foreclosure. (JEL G33)